DARIAH-HR digital tools in the frame of Open Science (PUBMET, 2023)
Responsibility, ethics, inclusiveness, and the principles of Open Science are central to the advancement of scholarly research and publishing. By embracing these values, we can create a more transparent, collaborative, and accessible research ecosystem, as proposed by UNESCO (2022). However, there is a pressing need for effective tools that aid researchers in practising Open Science while addressing the specific requirements of disciplines such as the Humanities and Arts, especially in the context of the welldocumented prevalence of STEM disciplines over the Humanities in the development of Open Science and Open Access trends (Eve, 2014). The Digital Research Infrastructure for the Arts and Humanities (DARIAH-EU) consortium, formed by "researchers for researchers", is uniquely positioned to address this inequality while driving the development of an open ecosystem that naturally evolves from authentic community practices and needs (Tóth-Czifra, 2021). Croatia as a member country with its DARIAH-HR coordination office readily follows it in this endeavour by organising workshops, creating one-of-a-kind digital platforms and tools, etc.In this poster presentation we aim to introduce several digital tools designed or codesigned by DARIAH-HR for scholars in the fields of the Humanities and Arts (and broader): 1) a digital tool for the creation of thesauri, 2) a digital tool for creating registers, 3) a digital tool for generating GDPR-compliant forms for obtaining consent from data subjects and 4) a software for modelling, processing and representation of monumental heritage and culture of memory. While the first and second tools represent pioneering efforts to encompass the widest community of humanists and researchers in Croatia, the third and fourth tools provide in-depth solutions in their respective areas of focus, extending their reach to an international level and catering to a diverse audience that includes researchers as well as tourists.The digital thesaurus creation tool “tezaurus.hr” is designed to streamline the process of developing structured vocabularies relevant to the Humanities and Arts. The digital register development tool “DH Register” provides a user-friendly interface (currently in development) that enables researchers to create and curate registries, incorporating metadata standards while adhering to the requirements of the FAIR principles (as recommended in, e.g., Hahnel & Valen, 2020). The “Consent Form Wizard” (CFW) is a tool developed by the DARIAH-EU working group Ethics and Legality in Digital Arts and Humanities (ELDAH) to support humanities researchers within the European Union in obtaining valid consent for data processing in the context of their specific professional activity. “Monument Heritage Map” is a digital platform that allows the implementation of available data and methods for data collection, processing, multimodal visualisation and mapping of cultural monuments.When integrated into an Open Science framework, these tools provide researchers with efficient means to enhance knowledge organisation, resource sharing, and collaboration while upholding responsible research practices and promoting inclusivity within the academic community. Enabling researchers to create user-friendly thesauri and registers also facilitates the discoverability, interoperability, and accessibility of research outputs. Conclusively, it contributes to the development of a robust and interconnected research infrastructure.Through the presentation of these digital tools and their implications, this poster seeks to contribute to the discourse surrounding responsible and inclusive research in the context of the Humanities and Arts. It emphasises the significance of training, education, and capacity building for Open Science.
Keywords: DARIAH-HR; digital tools; GDPR; Open Science; registers; thesauri